2014
DOI: 10.1080/02607476.2013.864019
|View full text |Cite
|
Sign up to set email alerts
|

How does writing for publication help professional development of teachers? A case study in China

Abstract: Publications by teachers reporting results or case studies of school-based teacher inquiry activities benchmark their professional development by indicating they have a 'stance of inquiry'. Such papers also disseminate valuable knowledge to the education community for sharing. Essay or case writing has always been a part of school-based teacher learning in China. The small-scale qualitative study reported here examines the impact of producing publications on the professional development of teachers within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…For example, Hall (2009) notes the relationship between teacher professional learning and the obligation to disseminate completed research on teachers' motivation to make informed decisions about their practices. Similarly, Wong (2014) found that producing publications about school-based inquiries contributed to teacher professional learning regarding student learning and insights into teaching practices.…”
Section: Origins and Locations Of Teacher Researchmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, Hall (2009) notes the relationship between teacher professional learning and the obligation to disseminate completed research on teachers' motivation to make informed decisions about their practices. Similarly, Wong (2014) found that producing publications about school-based inquiries contributed to teacher professional learning regarding student learning and insights into teaching practices.…”
Section: Origins and Locations Of Teacher Researchmentioning
confidence: 96%
“…Recurring benefits and challenges in teacher research: advantages, adversities and time as a constant constraint Looking across the different ways in which teacher research is sponsored, scholars have ascertained that conducting research within supportive conditions may enable teachers to contribute to the knowledge base of educational research while enhancing their professional learning and practice (Craig 2009, Wong 2014. The advantages associated with teacher research are numerous.…”
Section: Origins and Locations Of Teacher Researchmentioning
confidence: 98%
“…The issue of social justice is also hardly taught in teacher education as such, and that seems to be reflected in the ways teachers reflect on their job. Wong (2014) shows, for instance, how little engagement with the issue is to be noted in teachers' individual publications or research activities, which serve as schoolbased professional development in China. She writes: "To promote a research atmosphere in schools, local education departments and educational research institutes from the state and universities are responsible for discussing and determining research topics for some selected schools to conduct.…”
Section: China: From Structural Injustice To Micro-level Realitiesmentioning
confidence: 99%
“…Thus, the role of research in teacher education programs remains unclear ( Aspfors and Eklund, 2017 ). Similarly, little evidence exists on the research experiences and attitudes of English teachers although English teachers are increasingly required to conduct research on their practices whether or not they enroll in degree programs ( Wong, 2014 ; Yancovic-Allen, 2018 ; Byman et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%